Towards a European public sphere? A comparative study of the Facebook activities of Danish and Spanish members of the European Parliament - Valera-Ordaz, Lidia (El Profesional de la información, 2019)
This comparative study examines the everyday Facebook activities of all Danish and Spanish members of the European Parliament (MEPs), and the extent to which there is a real political conversation between citizens and European re- presentatives. Through content analysis, it analyzes the Facebook practices of a significantly under-studied population (MEPs) during a non-campaign period (January 15 to February 15, 2017) while most of recent research has overwhel- mingly focused on campaign periods. The results show that both Danish and Spanish MEPs are generously present and active on Facebook, but that they are less popular than their national counterparts. The study shows that Danish MEPs use Facebook in a clearly more dialogue-oriented way than their Spanish colleagues. Their updates often lead to conver- sations between followers, and they frequently take part in these political discussions, while Spanish MEPs tend to limit their Facebook practices to content publication, avoiding citizen conversation.